1995
DOI: 10.1111/j.1365-2958.1995.tb02427.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter selectivity control of Escherichia coli RNA polymerase by ionic strength: differential recognition of osmoregulated promoters by EσD and EσS holoenzymes

Abstract: Transcription in vitro of two osmoregulated promoters, for the Escherichia coli osmB and osmY genes, was analysed using two species of RNA polymerase holoenzyme reconstituted from purified core enzyme and either sigma D (sigma 70, the major sigma in exponentially growing cells) or sigma S (sigma 38, the principal sigma at stationary growth phase). Under conditions of low ionic strength, the osmB and osmY promoters were transcribed by both E sigma D and E sigma S. Addition of up to 400 mM potassium glutamate (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 32 publications
(11 reference statements)
9
83
1
Order By: Relevance
“…High concentrations of glutamate affect the activities of E 70 and E S holoenzymes differentially. Stimulation of E S holoenzyme and the concomitant repression of E 70 was observed using various promoters (Ding et al 1995;Rajkumari et al 1996). Selective activation of the E S holoenzyme was also found to be produced by trehalose, which accumulates in stationary phase E. coli (Kusano & Ishihama 1997a).…”
Section: Modulation Of the Transcription Apparatusmentioning
confidence: 95%
“…High concentrations of glutamate affect the activities of E 70 and E S holoenzymes differentially. Stimulation of E S holoenzyme and the concomitant repression of E 70 was observed using various promoters (Ding et al 1995;Rajkumari et al 1996). Selective activation of the E S holoenzyme was also found to be produced by trehalose, which accumulates in stationary phase E. coli (Kusano & Ishihama 1997a).…”
Section: Modulation Of the Transcription Apparatusmentioning
confidence: 95%
“…This promoter is recognized in vitro by the 70 -RNA polymerase holoenzyme (E 70 ) (10,55). Our group has also identified, by in vivo studies, another promoter located 250 nucleotides upstream of proV in E. coli (8,15) and has shown recently that this promoter is both RpoS ( S ) dependent and stationary-phase inducible (31).…”
mentioning
confidence: 92%
“…With regard to the cis elements mediating proU osmoresponsivity, there is a consensus on the existence of (i) a promoter whose transcription start site is approximately 60 nucleotides upstream of the initiation codon of the first structural gene (proV) (10,15,41,46,55) and (ii) a negative regulatory element (NRE) situated in a region overlapping the proximal (5Ј) end of proV whose deletion leads to a 25-fold derepression of proU expression at low osmolarity (8,13,30,40,42). This promoter is recognized in vitro by the 70 -RNA polymerase holoenzyme (E 70 ) (10,55).…”
mentioning
confidence: 99%
“…2B) stays almost at the same level, between 50 and 300 mM NaCl, indicating that transcription by these two holoenzymes is relatively resistant to inhibition by high NaCl concentrations. Previously, we found that high concentrations of glutamate enhance transcription by the E S and E F holoenzymes (6,22). Here we also examined the effect of increasing concentrations of potassium glutamate.…”
Section: Fecimentioning
confidence: 99%
“…Both E and FecI were extracted from the inclusion bodies with an extraction buffer containing 0.5% Triton X-100 and purified by Ni 2ϩ -nitrilotriacetic acid affinity chromatography. For reconstitution of the holoenzymes, we purified the -free core enzyme by chromatography of the purified RNA polymerase of E. coli W3350 (10) at least three times through phosphocellulose columns (6,22). The repeated chromatography is essential for complete removal of traces of minor subunits.…”
mentioning
confidence: 99%